1992
DOI: 10.1017/s0031182000074679
|View full text |Cite
|
Sign up to set email alerts
|

The role of nematode parasites in Soay sheep (Ovis ariesL.) mortality during a population crash

Abstract: In early 1989, two-thirds of the Soay sheep population on St Kilda died over 12 weeks. Post-mortem examinations revealed emaciated carcasses and considerable nematode burdens, with protein-energy malnutrition as the probable cause of death. Haematological and blood biochemical changes in the sheep, as well as fecundity of gastrointestinal nematodes, suggested the hosts were immunosuppressed. In parallel, laboratory experiments in which Soay sheep on a high plane of nutrition were artificially infected with Ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
318
1
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(330 citation statements)
references
References 50 publications
10
318
1
1
Order By: Relevance
“…The population exhibits a distinctive, unstable dynamic characterized by low and rising sheep numbers followed by high mortality (“crash”) winters in which more than half of the population may perish (Clutton‐Brock & Pemberton, 2004). High mortality winters are associated with strong selection on a range of phenotypic traits and are thought to result from a combination of low food availability due to competition, harsh winter climate conditions, and parasite pressure, predominantly from Strongyle gastrointestinal nematodes (GINs) (Coulson, 2001; Gulland, 1992; Gulland & Fox, 1992). Age‐related variation is well understood in this population, with differences evident between lambs, yearlings, prime age adults (2–6 years), and geriatrics (>6 years) in demographic rates and phenotypic traits both within and among the sexes (Coulson, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population exhibits a distinctive, unstable dynamic characterized by low and rising sheep numbers followed by high mortality (“crash”) winters in which more than half of the population may perish (Clutton‐Brock & Pemberton, 2004). High mortality winters are associated with strong selection on a range of phenotypic traits and are thought to result from a combination of low food availability due to competition, harsh winter climate conditions, and parasite pressure, predominantly from Strongyle gastrointestinal nematodes (GINs) (Coulson, 2001; Gulland, 1992; Gulland & Fox, 1992). Age‐related variation is well understood in this population, with differences evident between lambs, yearlings, prime age adults (2–6 years), and geriatrics (>6 years) in demographic rates and phenotypic traits both within and among the sexes (Coulson, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…As previous studies have suggested that overwinter survival varies with age, sex, August weight, and FEC, we initially examined the effects of these terms in our sample (Coulson, 2001; Gulland, 1992). We found evidence for a significant age‐by‐sex interaction (χ 2  = 9.84, P  = .02) with highest survival in female and adult groups, as expected.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these ITS data, there is no indication of a sister-group relationship between the St. Kilda and British samples. Unfortunately, definitive documentation of N. battus on St. Kilda is very recent (Gulland, 1992;Gulland and Fox, 1992), although an earlier report suggests that it may have been observed previously (Cheyne et al, 1974). Also, given the potential for more recent introductions of N. battus from the mainland via transport of other sheep breeds, it would seem unlikely that only sequences representing an early translocation and establishment would be found if additional sampling was performed on the archipelago.…”
Section: Geographic Samples Of N Battusmentioning
confidence: 99%
“…2011; Schmid‐Hempel 2011). Gastrointestinal nematodes (GIN) are ubiquitous and have important impacts on health in naturally occurring vertebrate populations (Gulland 1992; Albon et al. 2002; Cattadori et al.…”
Section: Introductionmentioning
confidence: 99%